Women with patellofemoral pain and knee crepitus have reduced knee flexion angle during stair ascent - Waiteman, Marina Cabral [UNESP] (2021)
Objectives: To compare trunk and knee biomechanics of women with and without patellofemoral pain (PFP) and knee crepitus during stair ascent. Design: Cross-sectional. Setting: Laboratory-based study. Participants: 29 women with PFP and knee crepitus (PFPCrepitus); 28 women with PFP and no knee crepitus (PFPNOCrepitus); 17 pain-free women with knee crepitus (Pain-freeCrepitus); and 29 pain-free women without knee crepitus (Pain-freeNOCrepitus). Main outcome measures: Peak trunk flexion, peak knee flexion, mean knee angular velocity, knee extensor moment at peak knee flexion, peak and impulse of the knee extensor moment. Results: PFPCrepitus group performed the stair ascent task with reduced peak knee flexion compared to Pain-freeCrepitus (p = 0.04; Effect size = −0.85) and Pain-freeNOCrepitus (p = 0.03; Effect size = −0.75). No significant differences among groups were found for peak trunk flexion (p = 0.979), knee angular velocity (p = 0.420), knee extensor moment at peak knee flexion (p = 0.933), peak (p = 0.290) and impulse (p = 0.122) of the knee extensor moment. Conclusion: Women with concomitant PFP and knee crepitus demonstrated reduced knee flexion during stair ascent, but no significant differences for trunk flexion and knee extensor moment variables were found.